Two new phytoparasitic hyphomycetes from Varanasi, India - and R.N. KHARWAR*, ARVIND KUMAR, ANUJ KUMAR (Indian Phytopathology, 2006)
Two new species of hyphomycetes from Varanasi, viz.,Cladosporium bauhiniana on fruits of Bauhinia variegata (Caesalpiniaceae), and Stenella cassinigena on living leaves of Cassia occidentalis (Caesalpiniaceae) respectively, have been described and illustrated.